Creative Work for Guitar Sonata of Isan Melodies - Weangsamut, Rattasat; Pikulsri, Chalermsak; Sapaso, Pongpitthaya (Rangsit Music Journal, 2022)
This article is a part of the research, the purpose of this research was to invent and explain how to play Sonata guitar of Isan melodies. The study suggested that Music composition of Sonata guitar in the first movement, was divided into three parts from the four Isan music instruments as follows. 1) Exposition, i.e., Wot SaoNoiYik Mae, Phin Po Pa Lan, and Khene Sud Sanae pattern, 2) Development by composing new music pattern, and 3) Recapitulation, i.e., Ponglang Ka Tenkon, which preserved the original pattern and the cultural identity tones, to be prolonged by employing the Music theory to compose the Sonata guitar music. The result suggests that Sonata guitar in Isan melodies was considered a high-quality and absoluteness. In addition, the song has explicitly transmitted the emotion of the local Isan music and cultural identity from regional music instruments of international. This study can be applied for further research and development in academic and commercial contexts in the future.